Nature Is a Transsexual Woman: Lucretian Metaphysics Reconsidered. - DeLire, Luce (Classical Philology, 2024)
Recent work shows that gender diversity is not a modern phenomenon. In this essay, I make a stronger claim: transsexuality is and always has been center stage, if only in an omitted form. More particularly, I argue that transsexuality lives at the heart of Lucretius' De rerum natura (DRN). Nature, to Lucretius, is female. And nature is a result of self-affirming productive interventions, embodied self-appropriation, fertilizing incision. Nature's femininity is both process and result of feminizing transition.